The Importance of Readability: A Guide to Understanding Alopecia Areata through Multilingual Online Resources - Tomasz Skrzypczak; Anna Skrzypczak; Jacek C. Szepietowski (Medical Journals Sweden, 2024)
Online resources play a vital role in patient education, yet the readability of alopecia areata-related materials remained understudied. A thorough analysis of online alopecia areata-related materials across 5 languages was conducted using Google search. Search terms "alopecia areata" and "alopecia areata treatment" were translated and queried, generating search result lists. The first 50 articles from each list were evaluated for suitability. The materials were categorized into 2 main groups: those focusing on alopecia areata itself and those addressing its treatment. Treatment materials were further divided into subgroups, including Janus kinase inhibitors and other treatment options. Readability was evaluated using the Lix score. The analysis included 251 articles in English, German, French, Italian, and Spanish. The overall mean Lix score was 52 ± 8, which classified them as very hard to comprehend. Articles on alopecia areata treatment had a mean Lix score of 55 ± 8, which was significantly higher (p < 0.001) than those on alopecia areata itself, 50 ± 8. alopecia areata-treatment articles dedicated to JAK inhibitors had an average Lix score of 57 ± 10 and it was significantly higher (p = 0.043) than those on other treatment, 53 ± 6. Online resources on alopecia areata and its treatments remained challenging to comprehend, particularly regarding JAK inhibitors. Improving clarity in patient education materials is crucial for informed decision-making and therapeutic relationships.